Prevalence of dental diseases in domesticated dogs - Sindayen, Julita Brillita H.
A preliminary study was conducted to determine the prevalence of dental diseases among domesticated dogs at the University of the Philippines Veterinary Hospital, in Diliman, Q)uezon City. Forty domesticated dogs of various breeds were selected through convenience sampling. Data collection was done through oral examination of the dog and interview with the pet owner. Oral examination was performed to determine if there were any existing disease states, and to detennine the general health status of the oral cavity, taking note of any disease processes, caries, plaque, soft tissue status and hard tissue status. Results showed that of the different dental diseases, caries and gingivitis were the most common disease among those examined, with prevalence rates of 70.5% and 80% respectively. Other oral conditions were noted: Presence of plaque - 80.5 %, Calcular deposits - 37.5%, Gingival recession - 20%, Malocclusion -10 %, Missing teeth - 10%, and Retained deciduous 2.5%. Dental disease is predominant in domesticated dogs. Diet, age and owner awareness seems to have an affect on the oral health status.